Cuban research on sea turtles (1994-2021): authorship, subject, and collaboration analysis - Thomas-Sánchez, Ruby (Iberoamerican Journal of Science Measurement and Communication, 2022)
This article analyzed Cuban research on sea turtles from a thematic and bibliometric perspective. This has been a mixed investigation in which bibliometric and content analysis techniques were applied. The Google Scholar database was used to retrieve documents. The authors with the highest productivity were those from the Fisheries Research Center (Cuba). The thematic areas most studied were: Studies in nesting areas (41%) and Conservation and management (25.6%). The south of the Guanahacabibes peninsula and the south of the Isla de la Juventud were the most examined geographical areas. The most studied species were: Chelonia mydas, Eretmochelys imbricata, and Caretta caretta. According to the centrality degree, the most important institutions were Cuban, standing out the Center for Fisheries Research, the Center for Marine Research, and the University of Havana. The most significant collaboration links were between the University of Havana-Marine Research Center, the National Company for the Protection of Flora and Fauna-Marine Research Center, the Marine Research Center-Fisheries Research Center, and the University of Havana-INSTEC. Through the thematic analysis, it was evidenced that there are geographical areas where sea turtles also nest. However, there are not many studies in this regard. Future research is recommended to deepen these issues for developing fisheries science in Cuba.